The Cathar myth of the fall. A late invention of independent heretical exegesis? - Czarnecki, Piotr (Studia religiologica, 2018)
Some scholars, following a deconstructivist interpretation of Catharism (which denies the existence of Catharism as dualistic heresy, or at least diminishes the significance of dualism as its distinctive feature) propose a hypothesis which assumes that Cathar dualism was not an idea imported from the East (from the earlier dualist traditions, especially from Bogomilism), but that it emerged indepen-dently in the West, later than it is reported by the sources, as an effect of specific scriptural exegesis developed in the dissidents’ schools. The main aim of this article is to verify, through the analysis of Biblical exegesis, this hypothesis, on which the myth of the fall – crucial for the dualist doctrine – was built. Based on various sources, both polemical and created by the Cathars themselves, it reconstructs biblical foundations of this crucial myth in two main branches of Catharism: the moderate and the radical (within the latter in two of its options: the angelic doctrine, and the doctrine of the two worlds), comparing them to the analogical exegetical concepts developed earlier by the Bogomils